Bedside risk stratification for mortality in patients with acute respiratory failure treated with noninvasive ventilation. Issue 2 (2nd April 2020) - Hayek, Adam J.; Scott, Vincent; Yau, Peter; Zolfaghari, Kiumars; Goldwater, Matthew; Almquist, Julie; Arroliga, Alejandro C.; Ghamande, Shekhar
Abstract: Our hypothesis was that patients managed with noninvasive ventilation (NIV) on the wards could be risk-stratified with initial pulse oximetry/fraction of inspired oxygen (SpO2 /FiO2 ) ratios and tidal volumes (Vte). A prospective study of consecutive patients with acute respiratory failure requiring NIV on the wards was conducted. A multivariate logistic regression model and a negative binomial regression model were used. A total of 403 patients (55.8% women) had a mean age of 65.0 ± 14.9 years with a mean body mass index of 32.1 ± 11.1 kg/m 2 . The 28-day mortality was 14.1%, and the intubation rate was 16.1%. Pneumonia was associated with the highest 28-day mortality (22.5%) and rate of intubation (36.7%) when compared with chronic obstructive pulmonary disease (4.4% and 7.3%) or congestive heart failure (22.2% and 13.4%). The SpO2 /FiO2 groups were <214 (26.6%), 214 -357 (66.0%), and ≥357 (7.4%). Those in the SpO2 /FiO2  < 214 group had a higher 28-day mortality rate (odds ratio [OR] = 8.19; 95% confidence interval [CI] 1.02 -65.7), intubation rate (OR = 3.7; 95% CI 1.1 -12.1), intensive care unit admission rate (OR = 2.9; 95% CI 1.2 -7.4), and length of stay (relative risk = 2.0; 95% CI 1.3 -3.0). A Vte/predicted body weight <7.7 mL/kg was associated with increased intubations (OR = 3.1; 95% CI 1.3 -7.4), intensive care unit admissions (OR = 2.5; 95% CI 1.3 -4.6), and 30-day readmissions (OR = 2.9; 95% CI 1.2 -6.8). In conclusion, in patients without acute respiratory distress syndrome who had acute respiratory failure managed with noninvasive ventilation on the wards, severe hypoxemia as assessed by a simple SpO2 /FiO2  ≤ 214 was associated with poor outcomes.